2022
DOI: 10.15252/emmm.202215795
|View full text |Cite
|
Sign up to set email alerts
|

Acetate supplementation restores cognitive deficits caused by ARID1A haploinsufficiency in excitatory neurons

Abstract: Mutations in AT‐rich interactive domain‐containing protein 1A (ARID1A) cause Coffin‐Siris syndrome (CSS), a rare genetic disorder that results in mild to severe intellectual disabilities. However, the biological role of ARID1A in the brain remains unclear. In this study, we report that the haploinsufficiency of ARID1A in excitatory neurons causes cognitive impairment and defects in hippocampal synaptic transmission and dendritic morphology in mice. Similarly, human embryonic stem cell‐derived excitatory neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Since inhibiting metabolic-epigenetic interactions by knocking out the nuclear metabolic enzyme ACSS2 exacerbates molecular and behavioral phenotypes observed in the mouse AD-tau model, we considered that stimulating this pathway by supplying the substrate of ACSS2, acetate, might have beneficial effects. Acetate supplementation to primary hippocampal neurons drives genes of learning and memory and promotes cognitive function in a developmental mouse model 42 , and acetate gavage can promote memory in the 5xFAD mouse 43 . To investigate and define mechanisms of acetate supplementation in modulation of gene function for learning and memory in normal mice, first we tested whether exogenous acetate is directly incorporated into hippocampal histone acetylation, using heavy labeled acetate.…”
Section: Acetate-enriched Diet Ameliorates Ad-tau Induced Molecular C...mentioning
confidence: 99%
“…Since inhibiting metabolic-epigenetic interactions by knocking out the nuclear metabolic enzyme ACSS2 exacerbates molecular and behavioral phenotypes observed in the mouse AD-tau model, we considered that stimulating this pathway by supplying the substrate of ACSS2, acetate, might have beneficial effects. Acetate supplementation to primary hippocampal neurons drives genes of learning and memory and promotes cognitive function in a developmental mouse model 42 , and acetate gavage can promote memory in the 5xFAD mouse 43 . To investigate and define mechanisms of acetate supplementation in modulation of gene function for learning and memory in normal mice, first we tested whether exogenous acetate is directly incorporated into hippocampal histone acetylation, using heavy labeled acetate.…”
Section: Acetate-enriched Diet Ameliorates Ad-tau Induced Molecular C...mentioning
confidence: 99%
“…16 However, due to the presence of haploinsufficiency, ARID1A loss of function could also be a result of copy number deletion. 17,18 This indicated that GC patients with either ARID1A point mutation or copy number deletion might refer to the same entity. Thus, in this study, we defined ARID1A loss as either point mutation or copy number deletion and analyzed the clinicopathologic, genomic, and immunophenotypic correlates of ARID1A-loss GC, which might give us a more comprehensive understanding for the impact of ARID1A alteration on GC and guide precision treatment for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In GC, our previous study revealed that somatic ARID1A mutation could predict superior response to fluorouracil‐based adjuvant chemotherapy (ACT) and anti‐PD1 immunotherapy 16 . However, due to the presence of haploinsufficiency, ARID1A loss of function could also be a result of copy number deletion 17,18 . This indicated that GC patients with either ARID1A point mutation or copy number deletion might refer to the same entity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our findings in human Fib-iNs would suggest the opposite strategy in the adult CNS, using Arid1a overexpression to increase regeneration. In excitatory human neurons derived from embryonic stem cells, ARID1A knockout results in decreased dendritic length and reduced synaptic markers (74), though only dendritic growth specifically was measured. Taken together, these and other studies have established a role for ARID1A in pioneer axon growth, dendritic complexity, and synaptic density.…”
mentioning
confidence: 99%